Rancang Bangun Sistem Informasi Aplikasi Kasir Toko Deli Jaya Martubung (Deli Jaya Martubung Store Cashier Application Information System Design) - Waruwu, Alfonsus Christopher; Kurniawan, Helmi (CV. ITTC INDONESIA, 2024)
Crowds of buyers in a shopping area can result in long queues at the cashier's desk. This long queue is often caused because the cashier is very slow in calculating the buyer's groceries. The slowness of the cashier in carrying out their duties, namely calculating the price of goods is caused by the fact that some of the selling prices of goods are not known by the cashier so that queues often become a problem in shopping places. For this reason, it is necessary to build a system that can assist cashiers in carrying out their duties, especially to find out the selling price of an item. This system uses an acronym in the world of programming, namely CRUD. This system will later be used by the cashier to store, display, change, and delete item data in the database. Thus the cashier does not need to memorize the selling price of each item.